بإستخدام المحلل الشبكي Ca1-xNixFe2O4 دراسة الخصائص الكهربائية والمغناطسية والإمتصاصية لفيرايت السبينل نوع - هاشم علي يسر; رسل يوسف ثامر; حسن عبد ياسر (University of Thi-Qar Journal of Science, 2019)
In this work, the spinal ferrite  has been prepared where  ,  used. as radar absorbing materials (RAM). Conventional ceramic techniques method was used to prepare these materials at  microwaves with the range of frequencies (8-12) GHz. The absorption for microwaves was examined by the utilized the network analyzer. The relationship between reflectivity, absorption and attenuation coefficient were plotted as a function of frequency, and sintered at a temperature . The results showed the emergence of several resonance peaks at , samples showed high Absorbency in contrast low reflectivity and high values of attenuation coefficient at the same frequencies, this is due to domain rotation as well domain wall motion of the ferrite. The values of the real and imaginary parts of relative magnetic Permeability and relative electric permittivity were measure for all samples. The results revealed the apparent resonance peaks at same frequencies that apparent at absorption and reflectivity curves of the same samples. X-ray diffraction tests were made for one sample and result showed the structure of the sample is polycrystalline.في.هذا البحث تحضير سلسلة من فيرايت  السبينل نوع  حيث  تأخذ القيم  بزيادة مقدارها  كمواد ماصة للأشعة الرادارية. تم إستخدام الطريقة السيراميكية التقليدية في تحضير العينات والتي تم تلبيدها بدرجة حرارة واحدة  درست إم تصاصية العينات ضمن النطاق السيني حيث مدى التردد بإستخدام جهاز المحلل الشبكي. رسمت العلاقة بين ألإمتصاصية، الإنعكاسية، معامل التوهين، النفاذية المغناطيسية و السماحية الكهربائية كدوال للتردد عند النطاق السيني. بينت النتائج ظهور عدة قمم رنينية عند ترددات النطاق السيني, أظهرت العينات إمتصاصية عالية وقيم معامل التوهين عالية في المقابل إنعكاسية قليلة والسبب هو دوران الحقل المغناطيسي نتيجة حركة جدار الحقل المغناطيسي للفيرايت. من قياسات النفاذية المغناطيسية وثابت العزل وضحت النتائج وجود القمم الرنينية عند نفس الترددات التي ظهرت عند منحنيات الإمتصاصية والإنعكاسية.  تم فحص حيود الأشعة السينية  للعينة  حيث أظهرت النتائج أن تركيب العينة هو متعدد التبلور.